Relieving the Tension: Lay Immigration Lawyering and the Management of Legal Violence. Issue 4 (29th October 2018) - Longazel, Jamie
Abstract : The Recognition and Accreditation Program (R&A Program) authorizes certain non‐lawyers, or "Accredited Representatives" (ARs), to practice immigration law out of non‐profit or faith‐based organizations. Drawing on interviews with practicing ARs, I describe how, at the center of this group's approach to legal practice, is a firm commitment to their clients. ARs report being particularly attuned – thanks to their social position and life experiences – to the hardships many of their clients confront at the hands of a punitive U.S. immigration system. I find this translates, on one hand, into an anti‐formalist legal practice: ARs describe performing emotional labor in order to take the edge off of formalism's rigidity for their clients. Yet at other times, cognizant of the high costs associated with a legal error, ARs describe being much more formalistic, prioritizing legal tedium. The picture becomes more complex when considered in the context of devolution and immigration governance, where it seems the emotional and bureaucratic work ARs do to protect their clients may also be providing ancillary benefits to the state. I conclude by reflecting on the implications this research has for scholarship on the legal profession, for research on "access to justice, " and for understandings of immigration governance.